Proteomic characterization of the hyaluronidase (e.c. 3.2.1.35) from the venom of the social wasp polybia paulista - Pinto, José Roberto Aparecido Dos Santos [UNESP] (2012)
Polybia paulista wasp venom possesses three major allergens: phospholipase A1, hyaluronidase and antigen-5. To the best of our knowledge, no hyaluronidase from the venom of Neotropical social wasps was structurally characterized up to this moment, mainly due to its reduced amount in the venom of the tropical wasp species (about 0.5% of crude venom). Four different glycoproteic forms of this enzyme were detected in the venom of the wasp Polybia paulista. In the present investigation, an innovative experimental approach was developed combining 2-D SDS-PAGE with in-gel protein digestion by different proteolytic enzymes, followed by mass spectrometry analysis under collision-induced dissociation CID) conditions for the complete assignment of the protein sequencing. Thus, the most abundant form of this enzyme in P. paulista venom, the hyaluronidase-III, was sequenced, revealing that the first 47 amino acid residues from the N-terminal region, common to other Hymenoptera venom hyaluronidases, are missing. The molecular modeling revealed that hyaluronidase-III has a single polypeptide chain, folded into a tertiary structure, presenting a central (β/α)5 core with alternation of β-strands and α-helices; the tertiary structure stabilized by a single disulfide bridge between the residues Cys189 and Cys201. The structural pattern reported for P. paulista venom hyaluronidase-III is compatible with the classification of the enzyme as member of the family 56 of glycosidase hydrolases. Moreover, its structural characterization will encourage the use of this protein as a model for future development of component-resolved diagnosis'. © 2012 Bentham Science Publishers.